Prevention and treatment of preterm delivery in pregnant women with isthmic-cervical incompetence - V. F. Bezhenar; F. R. Kuchukova; Z. Kh. Uzdenova (Акушерство, гинекология и репродукция)
Preterm delivery (PD) is a global public health problem, being the leading cause of perinatal morbidity and mortality in many countries. Despite numerous studies on the etiology of this condition, PD incidence has been increasing annually, and about 15 million infants are born prematurely (before the week 37 of gestation) worldwide. One of the main risk factors for PD is isthmic-cervical incompetence (ICI), which leads to microbial invasion of the amniotic cavity, prolapse of the fetal bladder, premature discharge of amniotic fluid and PD. Currently, several methods for ICI prevention and treatment are available: conservative (use of progesterone, obstetric pessary) and surgical (transvaginal cerclage and transabdominal cerclage).